Use of an Edaphic Microarthropod Index for Monitoring Wildfire Impact on Soil in Mediterranean Pine Forests - Chiara Lisa; Donatella Paffetti; Enrico Marchi; Susanna Nocentini; Davide Travaglini (Frontiers in Forests and Global Change, 2022)
The aim of this study was to investigate the potential of the Biological Soil Quality index (QBS-ar index) for monitoring the impact of wildfires on Mediterranean pine forests soils. The QBS-ar is a simplified eco-morphological index, based on edaphic microarthropods. We analyzed the QBS-ar values of pine stands burned one or two times and at different time spans from fire (from 10 days to 11 years after fire), in comparison to the unburned control area. Effect of fire on the biological soil quality evaluated with QBS-ar index was analyzed using univariate and multivariate techniques. Our results showed a significant variation of QBS-ar values between burned areas and those never burned. The impact of fire on the QBS-ar index and the microarthropod community was higher in the areas burned twice. A relevant average dissimilarity of taxonomic groups was found between the control area and the area burned twice, but also between the control area and the one observed 3 months after the fire. The taxa that contributed more to the dissimilarity were Pseudoscorpiones and Diplopoda, which reduced their presence after fire. Our study shows that the QBS-ar index is a dependable method for monitoring the impact of fire on soil quality in forest ecosystems and indicates that edaphic microarthropods communities in these Mediterranean pine forests return to the before fire condition 11 years after fire. The QBS-ar index could therefore be a useful tool for monitoring forest ecosystem rehabilitation after fire.